Cost Analysis of Oral Cancer Treatment in a Tertiary Care Referral Center in India - Ramireddy, Jeba Karunya; Sundaram, Daniel Sathiya; Chacko, Rabin K (Asian Pacific Journal of Cancer Biology, 2017)
Introduction: As much as the number of oral cancer patients is a heavy burden to the health care system in India, so much is the economic burden to the patient and the relatives, especially in India where most do not have any financial cover for their medical expenditure. Objectives: To find out the approximate cost of treatment of oral cancer through various modalities, and calculate the proportion of direct and indirect expenses, and then identify the factors which would increase the indirect expenses so as to come up with recommendations which will reduce the indirect cost thereby reducing the financial burden to the patient. Methods: A retrospective observational study was done in a tertiary care center for cancer treatment and the direct cost (medical expense), indirect cost (non-medical expense) incurred by the patients, their economic status and source of fund for payment of the expenses were obtained. Results: The proportion of indirect cost was about 38.72% of the total cost for patients who underwent a single modality treatment with surgery, around 34.73% for a combination treatment with surgery and RT (Radiotherapy), about 79.63% for treatment with conventional Radiotherapy without surgery and about 49.61% for treatment with IMRT (Intensity Modulated Radio Therapy) without surgery. Availability of financial aid or cover is abysmally poor. The rate of discontinuance of treatment is also very high according to this study. Conclusion: The proportion of the indirect cost is very high and the total expenditure can be reduced by approximately 30% by following measures discussed in this article.